DAMPAK PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP ETIKA BERBICARA PADA SISWA KELAS IX DI MTS GERPEMI TEBAS TAHUN 2025-2026 - Andre; Nuraini; Sera Yuliantini (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
This study aims to describe the impact of TikTok social media usage on the speaking ethics of ninth-grade students at MTs.S Gerpemi Tebas. The research focuses on three aspects: (1) how patterns of TikTok usage influence students’ speaking ethics, (2) the positive and negative impacts of TikTok on students’ speaking behavior, and (3) the preventive and educational measures taken by teachers to address the effects of TikTok on students’ speaking ethics. This study employed a descriptive qualitative approach using interviews, observations, and documentation as data collection techniques. The findings reveal that students use TikTok for approximately 8–12 hours per day, which significantly exceeds the ideal daily screen time of 4 hours and 17 minutes suggested by the University of Oxford. Students’ active engagement on the platform is reflected in the large number of followers they have, ranging from hundreds to thousands, as well as their frequent involvement in creating and consuming content. These usage patterns have influenced their communication habits and speaking styles in both school and social environments. The study also found that TikTok has both positive and negative effects on students’ speaking ethics. The positive impacts include increased creativity, greater self-confidence, enhanced communication skills, and broader knowledge gained from educational content. However, negative effects were also identified, including a decline in politeness, the use of inappropriate or harsh language, reduced concentration on academic activities, procrastination in completing school assignments, and social media addiction. These negative consequences have the potential to affect students’ academic performance and interpersonal relationships. To minimize these adverse effects, teachers, particularly Islamic Religious Education (PAI) teachers, have implemented several preventive and educational strategies. These efforts include collaborating with parents to monitor students’ social media activities, conducting regular mobile phone inspections at school, and providing guidance on proper speaking ethics based on Islamic values and teachings. Furthermore, when students consistently display inappropriate speaking behavior, parents are invited to participate in counseling and guidance sessions. These measures are intended to encourage responsible social media use, strengthen students’ awareness of ethical communication, and reduce the negative influence of TikTok on their daily lives.